2018
DOI: 10.1016/j.ejso.2018.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Individual data meta-analysis for the study of survival after pulmonary metastasectomy in colorectal cancer patients: A history of resected liver metastases worsens the prognosis

Abstract: A history of liver metastases is a negative prognostic factor for survival in patients with lung metastases from colorectal cancer. We registered the meta-analysis protocol in PROSPERO (CRD42015017838).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…This advantage of location in the upper lung was found even for OS, indicating the possibility of good outcomes for patients with left upper lobe oligometastases. Metastasectomy analyses performed in a previous study showed that patients who received wedge resection had shorter survival than patients who received lobectomy [ 17 ]. However, it has been shown that lobectomy of the left upper lobe was a risk factor for cerebral infarction because of thrombosis in the pulmonary vein stump, which has been reported to occur in 13.5% of patients after left upper lobectomy [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This advantage of location in the upper lung was found even for OS, indicating the possibility of good outcomes for patients with left upper lobe oligometastases. Metastasectomy analyses performed in a previous study showed that patients who received wedge resection had shorter survival than patients who received lobectomy [ 17 ]. However, it has been shown that lobectomy of the left upper lobe was a risk factor for cerebral infarction because of thrombosis in the pulmonary vein stump, which has been reported to occur in 13.5% of patients after left upper lobectomy [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…A history of local therapy for prior oligometastases, also known as metastasis-directed therapy, showed significant associations with LC, FFFM, RFS and OS, while the SBRT treatment period was significantly associated only with OS. Although prior oligometastatic sites were not investigated in this study, a history of liver metastases has been reported to be a negative prognostic factor for survival after surgery [ 17 ]. Potential micrometastases might gradually acquire resistance to radiotherapy and chemotherapy through local therapy with or without chemotherapy for tangible oligometastases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over recent years, since Pastorino published the results of the International Registry of Lung Metastasis in 1997 (2), resection of lung metastasis from primary non-pulmonary cancer has become an essential part of the activity of thoracic surgery departments (6). While we are still waiting for the results of the first clinical trial on lung metastasis (PulMIC trial) (7), several case series (8,9) and metaanalyses (10,11) have focused on the factors that affect survival following metastasectomy seeking to bring the list of factors proposed by Pastorino up to date. At present, the three factors suggested in 1997 seem to remain valid: status of surgical margins, disease-free interval and number of lung metastases.…”
Section: Strengths and Weaknesses Of The International Registry Of Lung Metastasismentioning
confidence: 99%
“…Modern chemotherapy, and possibly biological agents, have played a major role in improving long-term outcomes after sequential liver and lung resections [1]. However, the reported survival rates vary considerably, and surgical treatment of patients with CRC liver and lung metastases has been challenged, due to controversial outcomes [16,20,21]. Different studies are difficult to compare, due to the differences in study plans, outcome measurements (e.g., starting from the first or last metastasectomy), and selection biases.…”
Section: Introductionmentioning
confidence: 99%